2002
DOI: 10.1016/s0378-1097(02)01072-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of partial tuf gene sequences for the identification of lactobacilli

Abstract: Comparative analysis of partial tuf sequences was evaluated for the identification and differentiation of lactobacilli. Comparison of the amino acid sequences allowed differentiation between species and also between the subspecies of Lactobacillus delbrueckii. The nucleotide sequence comparison allowed differentiation between other subspecies and between some strains. Lactobacilli from several collections and isolates from dairy samples were clearly identified by comparison of short tuf sequences with those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 14 publications
3
39
0
Order By: Relevance
“…Consequently, 16S rDNA sequence analysis might not be an appropriate replacement for DNA reassociation to define closely related taxa. Our results and those of previous studies (4,18,19,26,27) suggested that tuf gene analysis also could be a valid tool for inferring relationships among closely related bacterial species. The use of the tuf gene, as well as the recA gene, as a phylogenetic marker for LAB has the advantage that the amino acid sequences from these genes can be used to infer bacterial phylogenies, avoiding the problems associated with rRNAs and the likely overestimation of the relatedness of taxa with similar nucleotide differences, nonindependence of substitution patterns at different sites, and bias derived from different GϩC contents of microorganisms (8).…”
Section: B Animalis-b Lactis B Longum-b Infantis and L Johnsonsupporting
confidence: 84%
See 2 more Smart Citations
“…Consequently, 16S rDNA sequence analysis might not be an appropriate replacement for DNA reassociation to define closely related taxa. Our results and those of previous studies (4,18,19,26,27) suggested that tuf gene analysis also could be a valid tool for inferring relationships among closely related bacterial species. The use of the tuf gene, as well as the recA gene, as a phylogenetic marker for LAB has the advantage that the amino acid sequences from these genes can be used to infer bacterial phylogenies, avoiding the problems associated with rRNAs and the likely overestimation of the relatedness of taxa with similar nucleotide differences, nonindependence of substitution patterns at different sites, and bias derived from different GϩC contents of microorganisms (8).…”
Section: B Animalis-b Lactis B Longum-b Infantis and L Johnsonsupporting
confidence: 84%
“…It has been already applied to infer phylogeny in the genera Enterococcus (18), Mycoplasma (1), and Staphylococcus (28). In addition, in a very recent study, a comparative analysis of partial tuf sequences was evaluated for the differentiation of some Lactobacillus species (4). It fulfills all prerequisites to server as a suitable phylogenetic marker, such as very high genetic stability and a wide distribution (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 16S rRNA analysis can provide an overview of the phylogenetic relationships between the investigated lactobacilli that was largely confirmed by the other techniques applied. In multilocus sequence analysis of housekeeping genes, only three of the four genes allowed a clear separation of L. johnsonii from L. gasseri (rpoA and pheS, as suggested by Naser et al [38], and tuf, as suggested by Chavagnat et al [12], but not groEL, contrary to the report by Teng et al [52]). The two DNA-typing methods confirmed the close relationships within strains of the species L. johnsonii and allowed intraspecies strain differentiation, confirming earlier reports (59).…”
Section: Interspecies Differences In the Genusmentioning
confidence: 65%
“…The tuf and recA genes have been proposed as useful markers in inferring bacterial phylogeny (2,10,18) and have recently been successfully used to differentiate species and subspecies within various bacterial genera (3,7,8,17). Our results show that the sequence analysis of tuf and recA as well as restriction fragment length polymorphism (RFLP) analysis of the internal transcribed spacer (ITS) sequences are relatively simple and rapid methods by which B. lactis and B. animalis can be identified without resorting to the use of species-specific PCR primer sets.…”
mentioning
confidence: 99%